TRANSFORMASI BUDAYA PENDIDIKAN AGAMA ISLAM DALAM DINAMIKA DIGITAL KONTEN SOSIAL MEDIA & ARTIFICIAL INTELLIGENCE (AI) (Qolamuna: Keislaman, Pendidikan, Literasi dan Humaniora, 2026)
This research investigates how Islamic Religious Education (PAI) has undergone cultural shifts amid the expanding influence of social media and Artificial Intelligence (AI). Using a qualitative methodology grounded in systematic literature review, the study draws on scholarly publications from 2023 to 2025. Three key findings emerge: first, the digitalization of PAI constitutes not a simple change of instructional tools, but a far-reaching cultural reimagining of the Islamic education system that compels educators to develop strong digital competencies alongside their command of Islamic content; second, platforms including YouTube, Instagram, and TikTok have evolved into vital arenas for Islamic pedagogy and da’wah among Generation Z, while also introducing substantial hazards such as the spread of religiously unverified content and the rise of digitally prominent but poorly qualified preachers; third, although AI presents considerable promise through adaptive learning, automated grading, and real-time feedback, its application must be anchored in Islamic moral values derived from the principles of maqashid al-shari’ah. This research affirms that constructing an authentic yet flexible Islamic education ecosystem within Society 5.0 demands coordinated effort among teachers, educational institutions, government bodies, researchers, and families to responsibly navigate the accelerating pace of digital change.